Anthropometric measurements of the human distal femur: A study of the adult malay population - Abd. Aziz, Azian; Zulkifly, Ahmad Hafiz (Hindawi Publishing Corporation, 2013)
The distal femurs of 100 subjects (50 men, 50 women) from the Malay population aged between 19 and 38 years were scanned to measure the anterior-posterior (AP) andmedial-lateral (ML)width.ThemeanAP valueswere 64.02 ± 3.38mmand 57.33 ± 3.26mm for men and women, respectively, and the mean ML values were 74.91 ± 3.52mm and 64.53 ± 3.07 mm.We compared our data to that published previously for the Chinese and Indian populations. It was found that theMalay population had smaller distal femur than that of the Chinese but was larger than that of the Indian population (P < 0.05). In conclusion, although it is well established that Asians have a smaller distal femur size than that of the Western population, the variations in different Asian ethnicities may need to be considered when designing the appropriate knee implant.